2019
DOI: 10.18805/ijar.b-1077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chicken growth hormone (cGH) SNP genotypes on morphometric and growth traits of three chicken breeds in Nigeria.

Abstract: This study was conducted to identify the diversity of chicken growth hormone (cGH) single nucleotide polymorphs’ (SNP) and their association on morphometric and growth traits of three Nigerian chicken breeds namely Funaab Alpha (FA), Shikabrown (SB) and Nigerian local chicken (NLC). Morphometric traits measured include shank length (cm), breast girth (cm) and breast width (cm) while growth traits measured were final body weight, av. weight gain, feed intake and feed conversion ratio all at laying stages respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The result of this study compares favorably with the findings of (Osman et al 2017) which showed significant differences (P≤0.012) between the three chicken strains (Lohmann, Cobb 500, and Avian 48) with zero SNPs found and the Hubbard F15 strain, which contain three SNPs in PRL gene. Similarly, Okafor et al (2019) reported that the association of SNP genotypes showed no statistical association effects on all parameters evaluated, except for the CC genotype that was significantly associated with CA genotypes for shank length in the NIC.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…The result of this study compares favorably with the findings of (Osman et al 2017) which showed significant differences (P≤0.012) between the three chicken strains (Lohmann, Cobb 500, and Avian 48) with zero SNPs found and the Hubbard F15 strain, which contain three SNPs in PRL gene. Similarly, Okafor et al (2019) reported that the association of SNP genotypes showed no statistical association effects on all parameters evaluated, except for the CC genotype that was significantly associated with CA genotypes for shank length in the NIC.…”
Section: Methodsmentioning
confidence: 88%
“…However, to the best of our knowledge, this is the first work on SNP approach to the study of the Nigerian indigenous chicken prolactin gene and its association with Light Ecotype chicken's egg traits. Notwithstanding, association studies have been done on morphometric and growth traits in some breeds of the Nigerian chicken, including the indigenous birds (Okafor et al 2019;Bello et al 2020). In a recent study of Okafor et al (2019) the chicken growth hormone SNP was associated with morphometric and growth traits in the NIC in addition to Funaab Alpha and ShikaBrown.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation